Foucault, subjectivity and ethics: towards a self-forming subject - Skinner, Diane (Organization (London, England), 2013)
In this article, I examine self-formation through the activity of organic farming in a self-managing community. How do producing and consuming subjects organize their selves around the ‘false natural object’ (Veyne, 1997) that is organic? To inform this ethnographic account of self-formation, I draw on the work of Michel Foucault. A study is made of technologies of the self in the contemporary setting of a self-managing organic farming community without compromising the self-forming, self-regulating activity of the ethical subject presented by Foucault in his studies of Antiquity. I contend that the self is formed by the subject as a thinking and acting being through the modes of subjectivation and objectivation (Foucault, 2000a). The article contributes empirical support to theoretical studies that consider how Foucault’s texts account for the intervention of human subjects alongside sociological factors when exploring organizational issues (Bardon and Josserand, 2011; McKinlay and Pezet, 2010). It is recommended that a wider range of responses could be opened up in Foucault-inspired studies at other organizational sites, including the workplace, by exploring the self-formation of the subject as a starting point for understanding the importance of the individual alongside sociological factors.